2020
DOI: 10.18632/aging.103016
|View full text |Cite
|
Sign up to set email alerts
|

Long non-coding RNA TPT1-AS1 promotes angiogenesis and metastasis of colorectal cancer through TPT1-AS1/NF90/VEGFA signaling pathway

Abstract: LncRNAs have been proven closely correlated to tumor progression. A recent study identified LncRNA TPT1-AS1 (TPT1-AS1) as one of the liver-metastasis associated LncRNAs in colorectal cancer (CRC). In this study, we report that TPT1-AS1 is upregulated in CRC tissues, which is associated with poor prognosis. Functional assays unravel a pro-angiogenesis and metastasis role of TPT1-AS1. Mechanistically, Flexmap 3D assays reveal that TPT1-AS1 upregulates the VEGFA secretion in CRC cells. RNA immunoprecipitation and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 23 publications
2
26
0
Order By: Relevance
“…TPT1-AS1 (TPT1 antisense RNA 1) is located on chromosome 13 and has been reported to promote proliferation and metastasis in a variety of cancers [27,28]. Interestingly, our finding of TPT1-AS1 as a potential therapeutic target for OC is corroborated by the study of Wu et al, who recently showed that TPT1-AS1 induces OC tumor growth and metastasis [29].…”
Section: Discussionsupporting
confidence: 81%
“…TPT1-AS1 (TPT1 antisense RNA 1) is located on chromosome 13 and has been reported to promote proliferation and metastasis in a variety of cancers [27,28]. Interestingly, our finding of TPT1-AS1 as a potential therapeutic target for OC is corroborated by the study of Wu et al, who recently showed that TPT1-AS1 induces OC tumor growth and metastasis [29].…”
Section: Discussionsupporting
confidence: 81%
“… 81 lncRNA TPT1-AS1 directly binds nuclear factor 90 (NF90) and induces the interplay between NF90 and the VEGFA mRNA, thus enhancing VEGFA mRNA stability and facilitating CRC angiogenesis and metastasis. 82 Moreover, LINC00346 can bind to the ZNF655 mRNA by its Alu elements, thereby promoting the degradation of the ZNF655 mRNA in a Staufen1-mediated mRNA decay manner. Furthermore, ANKHD1 targets LINC00346 and elevates its stability.…”
Section: Angio-lncrs: Mechanisms Of Action In Cancersmentioning
confidence: 99%
“…TPT1-AS1 can promote angiogenesis and metastasis of colorectal cancer (14). Up-regulation of TPT1-AS1 expression can promote tumorigenesis and metastasis of epithelial ovarian cancer (15).…”
Section: Discussionmentioning
confidence: 99%